TRANSFER BUDAYA DAN IDEOLOGIS DALAM TERJEMAHAN THE HOLY QORAN - Muhammad Khoirul Anwar (Universitas PTIQ Jakarta, 2022)
This article aims to elaborate on the occurrence of cultural and ideological transfers from the translation of the interpretation of the Qur’an written by the Lahore Ahmadiyya figure, Maulana Mohammad Ali. The translation of the work of Tafsir Al-Qur’an is very much done from both Arabic and English Tafsir. The translation of The Holy Qur’an is the first translation of the Qur’anic interpretation carried out in Indonesia. HOS Tjokroaminoto as the translator of the work and part of the translation was published in 1928 with a preface from Haji Agus Salim. However, the translation project had to be stopped due to opposition from Muhammadiyah during the Sarekat Islam Congress in 1927. This translation was continued by A. Aziz and completed in 1939 but was not allowed to be published. Then in 1959 the Ministry of Religion of the Republic of Indonesia gave permission to publish a Javanese edition translated by R. Ng. H. Minhadjurrahman Djayasugita and Mufti Sharif. As for the Indonesian edition, it has just been published in its entirety from the translation of H.M Bachrun in 1978 from a revised edition which has been published several times until now.